2017
DOI: 10.1002/acn3.449
|View full text |Cite
|
Sign up to set email alerts
|

Biased numerical cognition impairs economic decision‐making in Parkinson's disease

Abstract: ObjectivePrevious findings suggest a context‐dependent bihemispheric allocation of numerical magnitude. Accordingly, we predicted that lateralized motor symptoms in Parkinson's disease (PD), which reflect hemispheric asymmetries, would induce systematic lateralized biases in numerical cognition and have a subsequent influence on decision‐making.MethodsIn 20 PD patients and matched healthy controls we assessed numerical cognition using a number‐pair bisection and random number generation task. Decision‐making w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…One important distinction between studies is that we administered only one trial on the stranger version, while Arshad et al had 20, therefore more trials may be necessary to get a clearer picture of the role that hemispheric asymmetries play in common economic games. Nevertheless, it is interesting that left-sided patients show this increase in prosociality both in the altruistic intertemporal choice tasks (implicit) in the present study and in the stranger version of the dictator game in the study by Arshad et al (2017). The underlying mechanism for this hemispheric asymmetry is unclear.…”
Section: Altruism and Disease Characteristicsmentioning
confidence: 51%
See 3 more Smart Citations
“…One important distinction between studies is that we administered only one trial on the stranger version, while Arshad et al had 20, therefore more trials may be necessary to get a clearer picture of the role that hemispheric asymmetries play in common economic games. Nevertheless, it is interesting that left-sided patients show this increase in prosociality both in the altruistic intertemporal choice tasks (implicit) in the present study and in the stranger version of the dictator game in the study by Arshad et al (2017). The underlying mechanism for this hemispheric asymmetry is unclear.…”
Section: Altruism and Disease Characteristicsmentioning
confidence: 51%
“…The underlying mechanism for this hemispheric asymmetry is unclear. Arshad et al (2017) suggested that this effect was due to biased numerical cognition, but this should have resulted in group differences in all conditions of the intertemporal choice task and the dictator game. Furthermore, while some evidence supports greater involvement of the right hemisphere in various prosocial tasks (Hare et al, 2010; Morishima et al, 2012), a recent meta-analysis of fMRI studies reported bilateral involvement (Cutler & Campbell-Meiklejohn, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations